Role of Glutaminase 2 in Promoting CD4+ T Cell Production of Interleukin‐2 by Supporting Antioxidant Defense in Systemic Lupus Erythematosus. Issue 7 (12th May 2022) - Hisada, Ryo; Yoshida, Nobuya; Orite, Seo Yeon K.; Umeda, Masataka; Burbano, Catalina; Scherlinger, Marc; Kono, Michihito; Krishfield, Suzanne; Tsokos, George C.
Abstract : Objective: Glutaminase (GLS) isoenzymes GLS1 and GLS2 catalyze the first step of glutaminolysis. GLS1 is requisite for Th17 cell differentiation, and its inhibition suppresses autoimmune disease in animals, but the function of GLS2 is not known. The aim of this study was to investigate the role of GLS2 in CD4+ T cell function and systemic lupus erythematosus (SLE) pathogenesis. Methods: We measured reactive oxygen species (ROS) levels, lipid peroxidation, and mitochondrial mass and polarization by flow cytometry, interleukin‐2 (IL‐2) production by a dual luciferase assay, and CpG DNA methylation of Il2 by a real‐time polymerase chain reaction system. The impact of the overexpression of wild‐type GLS1, wild‐type GLS2, or mutated GLS2 at the PDZ domain–binding motif in CD4+ T cells was examined. Furthermore, GLS2 expression in CD4+ T cells from lupus‐prone mice and patients with SLE was analyzed by Western blotting. Results: GLS2, but not GLS1, reduced ROS levels and lipid peroxidation and restored mitochondrial function in T cells. GLS2 promoted IL‐2 production through the demethylation of the Il2 promoter. Mutation of the PDZ domain–binding motif abated the ability of GLS2 to regulate IL‐2 and ROS levels. In lupus‐prone mice and patients with SLE, the expression of GLS2 was decreased in CD4+ T cells. Finally, GLS2 overexpression corrected ROS levels and restored IL‐2 production by CD4+ T cells from lupus‐prone mice and SLE patients. Conclusion: Our findings suggest that GLS2 has a crucial role in IL‐2 production by CD4+ T cells by supporting antioxidant defense, and they offer a new approach to correcting IL‐2 production by T cells in SLE.